A Low-Cost Marker-Based Optical Motion Capture System to Validate Inertial Measurement Units - Siaw, Teck Ung; Han, Yi Chiew; Wong, Kiing (2023)
Commercialized marker-based optical motion capture system like Vicon is very expensive and not widely available. In the development of inertial measurement units, Vicon is required only for validation so sourcing for expensive system is undesirable. In this letter, a low cost alternative, which is also a marker-based optical motion capture system, is proposed to serve the purpose of validating inertial measurement units. Basically, the proposed system uses a smartphone camera to capture the motions of red markers and then track the coordinates of the markers followed by calculating the angle. The proposed system has a low average root mean square error of 0.83° when the distance between camera and markers is 120 cm. The method to synchronize inertial measurement units and camera data is also described in this letter as the starting time and sampling rate of the two systems are most likely different.